2007
DOI: 10.1007/s10508-006-9123-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Masturbation and Associated Factors in a British National Probability Survey

Abstract: A stratified probability sample survey of the British general population, aged 16 to 44 years, was conducted from 1999 to 2001 (N = 11,161) using face-to-face interviewing and computer-assisted self-interviewing. We used these data to estimate the population prevalence of masturbation, and to identify sociodemographic, sexual behavioral, and attitudinal factors associated with reporting this behavior. Seventy-three percent of men and 36.8% of women reported masturbating in the 4 weeks prior to interview (95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
122
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(156 citation statements)
references
References 22 publications
29
122
2
3
Order By: Relevance
“…14 and 36.8% in the Great Britain. 15 The results of our study show that the frequency is lower than the Western countries in all groups. The research on masturbation frequency in Turkey is very limited.…”
Section: Discussionmentioning
confidence: 46%
“…14 and 36.8% in the Great Britain. 15 The results of our study show that the frequency is lower than the Western countries in all groups. The research on masturbation frequency in Turkey is very limited.…”
Section: Discussionmentioning
confidence: 46%
“…It is equally difficult to see how masturbation develops sexual interests, when greater masturbation frequency is so often associated with impaired sexual function in men (Brody & Costa, 2009;Das, Parish, & Laumann, 2009;Gerressu, Mercer, Graham, Wellings, & Johnson, 2008;Lau, Wang, Cheng, & Yang, 2005;Nutter & Condron, 1985) and women (Brody & Costa, 2009;Das et al, 2009;Gerressu et al, 2008;Lau, Cheng, Wang, & Yang, 2006;Shaeer, Shaeer, & Shaeer, 2012;Weiss & Brody, 2009). Greater masturbation frequency is also associated with more dissatisfaction with relationships and less love for partners (Brody, 2010;Brody & Costa, 2009).…”
mentioning
confidence: 99%
“…A study of married women found that PVI was related to both marital and sexual satisfaction, cunnilingus was unrelated and masturbating the male partner until orgasm was associated with both poorer marital and sexual satisfaction (Hurlbert & Apt, 1994). In a national probability British subsample (Gerressu et al, 2008) and in a Chinese subsample (Das et al, 2009), female masturbation was associated with a series of sexual difficulties, which was confirmed in a Chinese random sample (Lau et al, 2006) and among Arabic women (Shaeer et al, 2012). Also, as discussed above, women who never had PVI orgasm have more difficulties during childbirth (Baxter, 1974) and, as will be discussed below, PVI frequency was found to be protective against breast cancer, but condom use or coitus interruptus were associated with increased risk (Gjorgov, 1978(Gjorgov, , 1998Le, Bachelot, & Hill, 1989;Vessey, Baron, Doll, McPherson, & Yeates, 1983).…”
Section: Independent Confirmationsmentioning
confidence: 96%
“…Congruent with the view that vaginal orgasm has an adaptive role of reinforcing desire for PVI, vaginal orgasm and PVI frequency are consistently associated with sexual satisfaction, relationship satisfaction, greater sexual desire and less risk of sexual dysfunction (Brody, 2007b;Brody & Weiss, 2011b;Costa & Brody, 2007;Fugl-Meyer, Oberg, Lundberg, Lewin, & Fugl-Meyer, 2006;Nutter & Condron, 1983;Philippsohn & Hartmann, 2009;Tao & Brody, 2011;Weiss & Brody, 2009a). In contrast, other sexual behaviors are frequently uncorrelated or correlated with more sexual difficulties (Brody & Costa, 2009b;Brody & Weiss, 2011a;Costa & Brody, 2007;Das, Parish, & Laumann, 2009;Gerressu, Mercer, Graham, Wellings, & Johnson, 2008;Lau, Cheng, Wang, & Yang, 2006;Nutter & Condron, 1983;Philippsohn & Hartmann, 2009;Shaeer, Shaeer, & Shaeer, 2012;Tao & Brody, 2011;Weiss & Brody, 2009a). Although Prause ignores this literature in her review concluding that orgasm has no primary role in rewarding women's sexual behavior, her own data seemingly conform to the pattern: women who considered the vagina the most important site for orgasm (when compared to women for whom the clitoris was the most important site for orgasm) had more desire for sex with a partner, but not more desire for masturbation.…”
mentioning
confidence: 99%